Proxy re-signature scheme based on isomorphisms of polynomial - Hui-xian LI; Lu SHAO; Liao-jun PANG (Tongxin xuebao)
Most of the existing proxy resignature schemes were based on the hardness of big integer factoring,discrete logarithm,elliptic curve.However,none of them can resist the attack by a quantum computer.Motivated by these concerns,a new proxy resignature scheme was proposed.By employing secret affine transformations and homogeneous polynomials,the proposed scheme could implement the signature transformation with high-efficiency,and meanwhile it was secure against the attack by a quantum computer.The results of analysis showed that the proposed scheme was correct and consistent,and had the unforgeability in the random oracle model.Compared with the existing schemes,the proposed scheme not only inherits the resistance to quantum attack and high efficiency from the multivariate public key cryptosystems,but also has the properties of multi-use,transparent and private proxy.